2014
DOI: 10.1177/2158244014522073
|View full text |Cite
|
Sign up to set email alerts
|

Client Self-Assessment in Community Aged Care

Abstract: Self-assessment of support needs is a relatively new and under-researched phenomenon in domiciliary aged care. This article outlines the results of a comparative study focusing on whether a self-assessment approach assists clients to identify support needs and the degree to which self-assessed needs differ from an assessment conducted by community care professionals. A total of 48 older people and their case managers completed a needs assessment tool. Twenty-two semi-structured interviews were used to ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Clients interested in participating in the trial from these organisations were randomly assigned to the five clusters contained 198 participants at Baseline and 137 participants at the end of the trial (Figure 2a). The full protocol for the trial has been reported previously [9]. In order to be eligible, clients had to be in receipt of a commonwealth aged care package.…”
Section: The Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Clients interested in participating in the trial from these organisations were randomly assigned to the five clusters contained 198 participants at Baseline and 137 participants at the end of the trial (Figure 2a). The full protocol for the trial has been reported previously [9]. In order to be eligible, clients had to be in receipt of a commonwealth aged care package.…”
Section: The Case Studymentioning
confidence: 99%
“…The study was based on a cohort SW-CRT to evaluate an intervention designed for older people receiving domiciliary aged care. A detailed description of this study is beyond the scope of this article and has been published elsewhere [9]. Section seven provides a discussion and conclusion of the main points raised in the article.…”
Section: Introductionmentioning
confidence: 99%